Impedance based fault location in power distribution systems - Jia, Ke (2012)
This thesis presents an investigation into impedance based fault location methods which directly use the fault transient as an excitation source to provide fast and accurate fault locations in small distribution systems such as the modem marine and aircraft power systems which have Integrated Power System (IPS) configuration. Fast and accurate fault location on un-exposed power distribution lines is of vital importance to expedite service restoration and improving the reliability of the power system.